2009
DOI: 10.1089/lap.2009.0249
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Hiatus Hernia Repair and Simultaneous Sleeve Gastrectomy: A Novel Approach in the Treatment of Gastroesophageal Reflux Disease Associated with Morbid Obesity

Abstract: Obesity is associated with significantly increased risk of gastroesophageal reflux disease and recurrence of reflux symptoms following surgical intervention, compared to individuals with normal body-mass index (BMI). The severity of reflux symptoms and obesity is associated with a decreased quality of life. In this article, we report a novel approach to the treatment of morbid obesity and hiatus hernia in a 36-year-old female with a BMI of 40 kg/m(2) who failed the conservative treatment. A laparoscopic hiatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…These details include attention to the sleeve size and volume, avoidance of narrowing the gastric body or pylorus, and identification and repair of all associated hiatal hernias. 36,39,40,[43][44][45][46] One series demonstrated that attention to crural repair during LSG resulted in GERD remission in 73% and a decrease in the development of de novo GERD from 23% to 0%. 43 These series suggest that technical modification may have a major role in reducing the risk of postoperative GERD with LSG but require larger samples and longer follow-up periods.…”
Section: Discussionmentioning
confidence: 99%
“…These details include attention to the sleeve size and volume, avoidance of narrowing the gastric body or pylorus, and identification and repair of all associated hiatal hernias. 36,39,40,[43][44][45][46] One series demonstrated that attention to crural repair during LSG resulted in GERD remission in 73% and a decrease in the development of de novo GERD from 23% to 0%. 43 These series suggest that technical modification may have a major role in reducing the risk of postoperative GERD with LSG but require larger samples and longer follow-up periods.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to mention that the prevalence of hiatal hernia in the morbidly obese is nearly 40 % [45], suggesting that surgeons should evaluate whether patients need to have a hiatal hernia repair at the same time of sleeve gastrectomy, particularly if the patient has previous GERD symptoms [46][47][48]. In the robotic group, another factor that could explain a longer operative time was related to the fact that it was used as a surgical training model, Romero et al [37] reported a length of stay in the robotic group of 2.2 days compared to 3.3 days in the systematic review (p=<0.005).…”
Section: Discussionmentioning
confidence: 99%
“…There are also articles in the literature reporting that HHR was performed safely with a mesh after SG [21,22]. In our study, no prosthetic material was used in any patient.…”
Section: Discussionmentioning
confidence: 79%